The Influence of Service Quality, Product Quality Toward Brand Image with Customer satisfaction as Intervening Variable (Case Study at Agency Customers of PT. Prudential Life Assurance) - -, Rhomadona; Fionita, Ita (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Brand image is a perception that is in customer’s mind. Through Brand Image, customers can experience and get recognize the product, evaluating the quality, lower purchasing risk, and get a certain satisfaction from product differentation. One of Strategy that is widely used by companies is by increasing Brand Image. The creation of brand image providing benefits in the success of a business engaged in services. Incurance companies are demanded to always cleanup seriously by increasing customer satisfaction that can be achieved through the creation of good service and product that can produce good corporate brand image. This research was aimed to know the influence of service quality and product quality onbrand image through customer satisfaction as intervening variable that functions as connector between independence variable namely service quality, product quality, and dependence variable namely brand image. Research methodology used in this research was associative. The research sample was taken by probability sampling is proportionate stratified random sampling. Hypothesis testing with 95% confidance level. The result of this research indicated that service quality, product quality have a significant influence onbrand image with customer satisfaction as connecting variable.Key Words : Service Quality, Product Quality, Brand Image, Satisfaction, Intervening